Trace-level analysis of geosmin in aquaculture systems by Headspace SPME-GC-MS/MS - Shi-Zhan Tang; Zhong-Xiang Chen; Li Huang; Chen-Hui Li; Ning-Ning Du; Jing Ren; Dong-Li Qin; Peng Wang (MethodsX)
The persistent challenge of earthy off-flavors in aquatic systems stems largely from geosmin (GSM), a microbial metabolite with an exceptionally low human detection threshold. This compound poses significant organoleptic and economic impacts on both aquaculture operations and municipal water supplies. To enable precise GSM monitoring, we optimized a sensitive headspace solid-phase microextraction coupled with gas chromatography-tandem mass spectrometry (HS-SPME-GC–MS/MS) method. The results indicate that the optimal experimental conditions include the addition of 2.0 g NaCl, magnetic stirring at 1000 rpm, and headspace extraction at 60 °C for 40 min. The ion pairs 112/97 and 112/83 were selected for the qualitative and quantitative analysis of GSM, with optimal collision energies of m/z 97 (CE 10 V) and m/z 83 (CE 10 V). Under these conditions, the method demonstrated excellent precision, accuracy, and sensitivity, facilitating the detection of trace residues of GSM in fishery water environments. • GSM was detected by HS-SPME-GC–MS/MS high selectivity, trace detection. • The detection limit was 0.31 ng/L, and the recovery rate was from 72.5 % to 111 %. • This provides a reliable and effective technical approach to mitigate water odor issues.